Aerobic exercise capacity is normal in obesity with or without metabolic syndrome. (April 2023) - Deboeck, G.; Vicenzi, M.; Faoro, V.; Lamotte, M.
Abstract: Background: Obesity might be a cause of limited aerobic exercise capacity. It is often associated with metabolic syndrome (MS) that includes cardiovascular comorbidities as arterial hypertension. Cardiopulmonary exercise testing (CPET) is the gold-standard to assess aerobic capacity and discriminate causes of dyspnea. Aim: To evaluate aerobic capacity in obesity and if MS or hypertensive treatment impacts on the CPET profile. Methods: CPET of 146 obese patients, whom 33 and 31 were matched for MS and antihypertensive medication, were analyzed. VO2peak (mL/min/Kg) was reported in percentage of predicted value, or, divided by body weight, fat free mass (FFM) or body weight expected for a body mass index of 24 (BMI24). Results: VO2peak (20, 8 ± 4, 4 mL/min/Kg) was normal when expressed in percentage predicted for obesity (111 ± 22%pred) or divided by FFM and weightBMI24 (33, 6 ± 5, 6 and 30, 6 ± 6, 2 respectively). The latter correlated better with maximal work rate (r = 0, 7168, p < 0, 001). Obese patients showed normal ventilatory efficiency (ventilation to carbon dioxide production slope: 28 ± 4), VO2 to work rate (10, 2 ± 1, 6 mLO2 /Watt) and, slightly elevated heart rate to VO2 slope (4, 0 ± 1, 1 bpm/mL/min/Kg). Compared to normotensives, hypertensive medicated patients had higher blood pressure at anaerobic threshold (142 ± 23 vs 158 ± 26 mmHg, p = 0, 001) but not at maximal exercise (189 ± 31 vs 201 ± 23 mmHg, p = NS), and, had lower actual maximal heart rate (155 ± 23 vs 143 ± 25 bpm, p = 0, 03). There was no difference between obese patients with or without MS. Conclusion: Obese people with or without MS present with similar and normal aerobic profile related to the excessive body weight. VO2peak divided by weightBMI24 is an easy and clinical meaningful index for obese patients. Highlights: Obese patients present with normal cardiopulmonary exercise adaptation. Metabolic syndrome does not impact cardiopulmonary exercise adaptation. VO2 peakBMI24 is a meaningful index of aerobic capacity.